HUBUNGAN ANTARA PROFESIONALISME GURU PAI DENGAN INTENSITAS IBADAH SISWA SMA NU JUNTINYUAT KABUPATEN INDRAMAYU - Zamzami, Zamzami; Rokhman, Asep Saepul (Khulasah : Islamic Studies Journal, 2021)
In educational activities at school, a teacher is the spearhead of success in teaching and learning activities. So, he is required to be professional. Mohamad Surya states in the Draft Law on Teachers (article 14) that: "Professional is the ability to carry out work in accordance with one's skills and dedication to other parties." Professional teachers are teachers who have received formal recognition based on applicable provisions, both in relation to with their position and formal educational background. Mohamad Surya said "Teachers are professional educators with the main task of educating, teaching, guiding, directing, training, assessing and evaluating students in formal education as well as at the primary and secondary education levels." Education is a conscious effort to grow and develop the potential of Human Resources through teaching activities. These teaching activities are held at all levels of nine-year basic education, secondary education and higher education. This research seeks to reveal the relationship between PAI teacher professionalism and the worship intensity of NU Juntinyuat High School students, Indramayu Regency. The Islamic Religious Education Teacher is a figure who has direct responsibility for developing children through the learning process in the classroom, so that he will make a big contribution to the student's worship process. Data collection is carried out through observation, interviews, documentation and questionnaires, so that the data collected in an integrated manner can complement each other. And data analysis techniques are processed statistically, using the product moment correlation formula. From the results of data analysis, the following conclusions were obtained: the professionalism level of Islamic Religious Education teachers at SMA NU Juntinyuat, Indramayu Regency obtained an average score of 3.7. is in the sufficient category. 2). Student worship achieves sufficient results when measured and daily student behavior reaches an average score of 3.4 (located in the interval 3.1 — 4.0. 3). Correlation analysis between the professionalism of Islamic Religious Education teachers and students' worship intentions obtained an r-calculated value of 0.3 11, this value is at a low level of correlation. This means that there is a low correlation between the variable teacher professionalism and student worship intensity.